Nilai-Nilai Pancasila dalam Ajaran Kearifan Lokal Islam Masade - Fadhlurrahman, Imaduddin (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
Research  on  the  teachings  of  Islam  Masade  in  Sangihe,  North  Sulawesi is a study to understand  Islam Masade as a local belief and to assess the  ethical values  contained in the teachings of Masade Islam. The core teachings of  Islam  Masade  is  obedience  to  God.  Perfection  in  the  teachings  of  Islam  Masade  when  carrying  out  the teachings  and  commands  of  God. Perspective  used  in  this study is the Pancasila Ethics because it is an ethical vision in life. This  research  is  a  library  research  using  philosophical  hermeneutics  method. Primary and secondary sources were examined using elements including decryption,  verstehen,  hermeneutics,  and  critical  reflection. The  object  of  this research is Islam Masade. The formal object in this research is Panasila Ethics. The   results   showed   the   following:   Ethical   values contained   in   the teachings  of  Islamic  Masade  are  Religious  Values, Cultural  Values,  and  State Values in  terms  of  the  Pancasila  Ethics  will  findGod  Values, Human  Values, Unity  Values,  Social  Values,  and  Fairness  Values.  These  ethical  values are important   in   national   life   because   they   conflict   with   the   ethical   vision   of Pancasila.AbstrakPenelitian  mengenai  ajaran Islam  Masade di  Sangihe,  Sulawesi  Utara merupakan  suatu  upaya  untuk  memahami Islam  Masade sebagai  kepercayaan lokal  dan  mengidentifikasi  nilai-nilai etis  yang  terkandung  dalam  ajaran Islam Masade.Inti   ajaran   dari Islam   Masade adalah ketaatan   kepada   Tuhan. Kesempurnaan  dalam  ajaran Islam  Masade ketika  melaksanakan ajaran  dan perintah  Tuhan. Perspektif  yang  digunakan  dalam  penelitian  ini  adalah  Etika Pancasila karena merupakan suatu visi etika dalam kehidupan.Penelitian    ini merupakan penelitian    kepustakaan    dengan    metode hermeneutika filosofis. Sumber-sumber primer dan sekunder diteliti menggunakan unsur-unsur  antara  lain  dekripsi, verstehen,  hermeneutika,  dan refleksi  kritis. Objek  penelitian  ini  adalah Islam  Masade. Objel  formal  dalam  penelitian  ini adalah Etika Panasila. Hasil penelitian menunjukkan hal-hal sebagai berikut: Nilai-nilai etis yang terdapat  dalam  ajaran Islam Masade adalah  Nilai  Religius,  Nilai  Adat-istiadat Kebudayaan, dan  Nilai  Kenegaraan  yang  apabila  ditinjau  dari  Etika  Pancasila akan  menemukan  Nilai Ketuhanan,  Nilai  Kemanusiaan,  Nilai  Persatuan,  Nilai Kerayatan,  dan  Nilai  Keadilan.  Nilai-nilai  etis  tersebut  penting  dalam  kehidupan bangsa karena sejalan dengan visi etika Pancasila.